Effect of Feeding Moringa oleifera Meal on Physiological and Haemato-Biochemical Profile of Surti Kids - Patel, Y G; Shah, S V; Modi, R J; Lunagariya, P M (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present experiment was conducted to study the effect of feeding Moringa oleifera meal by replacing compound concentrate mixture in Total Mixed Ration (TMR), on physiological and haemato-biochemical profile of twenty-four Surti kids. The kids were divided into four treatment groups viz., 0% (T1), 25% (T2), 50% (T3) and 100% (T4). The average respiration rates, heart rates and rectal temperature in T1, T2, T3 and T4 were found to be 38.44±2.65, 38.22±2.66, 37.56±2.32 and 40.44±2.69 breaths/min, 111.11±3.11, 112.44±3.00, 111.33±3.38 and 119.78±3.13 beats/min, and 101.66±0.11, 101.77±0.08, 101.82±0.12 and 101.45±0.11 °F, respectively. Amongst haemato-biochemical parameters, haemoglobin, serum total protein, glucose, cholesterol, SGPT, SGOT, Calcium and Phosphorus showed non-significant difference, while serum urea and creatinine differed significantly (p<0.05) between different groups. However, values of all the haemato-biochemical parameters were within normal physiological range in all the treatment groups.